The Burden of Keeping Things to Yourself: Self-Concealment and Suicidality - Hogge, Ingrid; Kim, Jisu; Kim, Eunha (Counselling Psychology Quarterly, 2023)
Suicide is a critical concern for psychologists given the complexity of suicide risk and fatal consequences. Using self-determination theory (SDT) as a framework, we examined the relationships between self-concealment, basic psychological needs, collectivism, and suicidality in a sample of adults in the United States (n = 199). Self-concealment is an interpersonal pattern of hiding sensitive personal information from others and has been correlated with increased suicidality. We tested a model whereby unmet basic psychological needs (i.e. autonomy, competence, and relatedness) mediated the relationship between self-concealment and suicidality. We also included collectivist cultural orientation as a moderator. We found that greater self-concealment was associated with more dissatisfaction with all three basic needs. However, only dissatisfaction with the relatedness need was associated with more suicidality. The effect of relatedness need dissatisfaction on suicidality was moderated by collectivism such that the effect was stronger for participants who were higher in collectivism. We found support for SDT as a framework for theory driven exploration of self-concealment and suicidality. The significant moderating effect of collectivism also highlights the importance of including cultural variables in future research. We include a discussion of implications for research, intervention, and prevention.
Keywords: collectivism; relatedness need; self-concealment; self-determination theory; suicidality